Visualisation tool to study malaria transmission using network modelling - Wong, Ji Yeh (Universiti Malaysia Sarawak (UNIMAS), 2014)
Malaria has been described as one of the major killer diseases. There were about 219 million cases of malaria in 2010 and an estimated 660,000 deaths. This deserves urgent scientific investigations and studies on malaria transmission. Since malaria is a vector borne disease, this project aims to produce a visualisation tool to model the disease transmission through formulating a heterogeneous bipartite contact network of two node types (public places and human beings). In addition, the Hypertext Induced Topical Search (HITS) web search algorithm was adapted to implement a search engine, which uses the bipartite contact network as the input. Java was used to implement the visualisation tool. The output from this visualisation tool shows predicted hotspots which harbour the infected malaria vectors. This output was validated with UCINET 6.0 as the benchmark system. A similar dominant node ranking output was obtained when the output from the benchmark system is compared with that of the modelling tool. The resulting information is believed helpful to tackle the issue of malaria transmission from the perspective of vectors detection.